A piezoelectric sensor network with shared signal transmission wires for structural health monitoring of aircraft smart skin. (July 2020) - Wang, Yu; Qiu, Lei; Luo, Yijie; Ding, Rui; Jiang, Fei
Highlights: A kind of PZT sensor network is proposed and implemented by a unique wiring method. Only M + N wires and monitoring channels are required for the M × N PZT sensor network. The sensor network can greatly reduce the number of wires and monitoring channels. Simple and reliable impact and damage monitoring methods are proposed and verified. A 7×7 PZT Layer is also designed and manufactured for functional verification. Abstract: Aircraft smart skin needs to integrate a large number of piezoelectric (PZT) elements and wires for structural health monitoring (SHM), which not only add considerable weight to aircraft structures, but also occupy a lot of monitoring channels, making the monitoring system complex. To study this issue, this paper proposed the design method of a PZT sensor network with shared signal transmission wires and its passive and active SHM methods. The design principle is that one electrode of each PZT in the same column are connected by the same wire and the other electrode of each PZT in the same row are connected by the same wire. Compared with a conventional M × N PZT sensor network, which requires at least M × N wires, the proposed PZT sensor network with shared signal transmission wires only requires M + N wires without increasing PZTs. A 7 × 7 PZT Layer with shared signal transmission wires is designed and manufactured by the Flexible Printed Circuit (FPC) process to further reduce the weight. The PZT Layer with an effective monitoring region of 780 mm × 780 mm is co-cured onto a glass fiber reinforced plate for verification. Experimental results show that the PZT Layer can accurately detect structural impact and damage regions based on the SHM methods, demonstrating that the proposed PZT sensor network with shared signal transmission wires can significantly reduce the number of wires and monitoring channels and has great potential in aircraft smart skin applications for both passive and active SHM.